Teka Stańczyka. - Koźmian, Stanisław (1836-1922); Szujski, Józef (1835-1883); Tarnowski, Stanisław (1837-1917); Wodzicki, Ludwik (1834-1894) (Redakcja Przeglądu Polskiego, 1870)
Rec. Jubileusz broszury / Ludwik Straszewicz // Kraj. Petersburg. - R.13, nr 52 (11 stycz. 1895).